(x+1)(2x-3)-(x-1)(x+2)=x的平方+7 解方程
1个回答
2X²-3X+2X-3-(X²+2X-X-2)=X²-7
2X²-X-3-X²-2X+X+2=X²+7
2X²-X-3-X²-2X+X+2-X²=7
-2X=8,即X=-4
相关问题
解方程 196x平方-1=0 4x平方+12x+9=81 x平方-7x-1=0 2x平方+3x=3 x平方-2x+1=2
解下列方程 x的平方-7x-1=0 2x的平方+3x=3
解方程(x平方+x-3)/(x平方+x-2)+1=(2x平方+4x+1)/(x平方+2x+1)
解方程(2x+1)(2x-1)+3(x+2)(x-2)=(7x-1)(7x+1)
2x的平方-7x=3解方程:2x²-7x=3
解方程:1/(x的平方+x)+1/(x的平方+3x+2)+1/(x的平方+5x+6)+1/(x的平方+7x+12)+1/
解方程:(x-3)(x+1)=x(2x+)-(x的平方+1)
解方程:(1)x的平方-7x+5=0 (2)3x的平方-4x-2=0
解不等式和方程!1.(x-1)(x+2)≤(x-2)(2x+1)2.1/(x+2)≤3解方程1.√(x+7)-x=1
解方程 (x+3)(x-2)-(x+1)的平方=-1